2009
DOI: 10.1897/08-375.1
|View full text |Cite
|
Sign up to set email alerts
|

Mercury‐selenium compounds and their toxicological significance: Toward a molecular understanding of the mercury‐selenium antagonism

Abstract: The interaction between mercury (Hg) and selenium (Se) is one of the best known examples of biological antagonism, yet the underlying mechanism remains unclear. This review focuses on the possible pathways leading to the Hg-Se antagonism, with an emphasis on the potential Hg-Se compounds that are responsible for the antagonism at the molecular level (i.e., bis[methylmercuric]selenide, methylmercury selenocysteinate, selenoprotein P-bound HgSe clusters, and the biominerals HgSe(x)S(1-x)). The presence of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
304
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 400 publications
(316 citation statements)
references
References 139 publications
10
304
0
2
Order By: Relevance
“…The most neurotoxic form of Hg that can be found in animals is the organic form, methylmercury e MeHg (Khan and Wang, 2009). Consuming fish elevated in MeHg causes adverse health effects ranging from neurodevelopmental deficits in offspring to increased risk of myocardial infarction in adults (Khan and Wang, 2009;National Research Council, 2000;Sunderland et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most neurotoxic form of Hg that can be found in animals is the organic form, methylmercury e MeHg (Khan and Wang, 2009). Consuming fish elevated in MeHg causes adverse health effects ranging from neurodevelopmental deficits in offspring to increased risk of myocardial infarction in adults (Khan and Wang, 2009;National Research Council, 2000;Sunderland et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It functions through selenoproteins such as glutathione peroxidase (Dorea, 2002), and protects animals from the toxicity of both inorganic Hg and MeHg (Khan and Wang, 2009). In higher-trophic marine animals, demethylation processes of MeHg are known to occur in the liver with a subsequent formation of HgSe granules (tiemannite), explaining the 1:1 M ratio of Se and Hg observed in these animals (Cuvin-Aralar and Furness, 1991; Koeman et al, 1973;Nigro and Leonzio, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the average Se/Hg molar ratios in the muscle of commercial shrimp were comparatively high (in the range of 16-106). Other studies reported that Se may counteract Hg toxicity and Se/Hg molar ratios above one may increase the protective effect of Se against MeHg exposure (Peterson et al, 2009;Khan and Wang, 2009). We showed that shrimp commercially available in Japan do not pose a particularly high risk regarding MeHg exposure to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…People consume Se mainly through seafood, with its organic form comprising the greatest proportion of total dietary intake (Agency for Toxic Substances and Disease Registry, 2003;Roman et al, 2014). Selenium plays an important role providing an antagonistic effect on Hg toxicity in various tissues and organs of rodents, fish and marine mammals (Peterson et al, 2009;Khan and Wang, 2009;Sakamoto et al, 2015). The correlation between Se concentrations in human specimens and health risk has been widely studied in the environmental health science of MeHg (Mozaffarian and Rimm, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has long been observed that Se protects animals from the toxicity of both inorganic Hg and MeHg. However, additive or even synergistic effects of Hg and Se have also been reported (Khan and Wang, 2009). Mechanisms of interaction of selenium with heavy metals are not yet completely elucidated (Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%